2000
DOI: 10.1094/phyto.2000.90.2.197
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Population of Phytophthora, Similar to P. infestans, Attacks Wild Solanum Species in Ecuador

Abstract: Twenty-six isolates of a Phytophthora population from two wild solanaceous species, Solanum tetrapetalum (n 11) and S. brevifolium (n = 15), were characterized morphologically, with genetic and phenotypic markers, and for pathogenicity on potato and tomato. Based on morphology, ribosomal internal transcribed spacer region 2 (ITS2) sequence, and pathogenicity, all isolates closely resembled P. infestans and were tentatively placed in that species. Nonetheless, this population of Phytophthora is novel. Its prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 24 publications
2
55
2
8
Order By: Relevance
“…The reasons for the fluctuations are unexplained. The results demonstrating that the A2 mating type was more frequent on potato than on tomato crops were in contrast to findings reported from other studies (Lebreton and Andrivon 1998;Lebreton et al 1999;Ordoñez et al 2000), and contradicts the evidence from other regions of an association between the host and the mating type by host-plant specificity (Ordoñez et al 2000). It seems that there are no obvious rules governing the A1:A2 ratio within the potato and tomato populations of P. infestans (or at least none we can identify), and the results found by different authors are casual.…”
Section: Discussioncontrasting
confidence: 99%
“…The reasons for the fluctuations are unexplained. The results demonstrating that the A2 mating type was more frequent on potato than on tomato crops were in contrast to findings reported from other studies (Lebreton and Andrivon 1998;Lebreton et al 1999;Ordoñez et al 2000), and contradicts the evidence from other regions of an association between the host and the mating type by host-plant specificity (Ordoñez et al 2000). It seems that there are no obvious rules governing the A1:A2 ratio within the potato and tomato populations of P. infestans (or at least none we can identify), and the results found by different authors are casual.…”
Section: Discussioncontrasting
confidence: 99%
“…The eight isolates in this group were characterized by Gpi 86/100, Pep 96/100, Ia mtDNA haplotype and an RFLP fingerprint different from any described previously (Table 2, Figure 2). The fingerprint lacked bands 2 and 24a, present in the EC-1 lineage, and had bands 18 and 19, previously described for the RFLP fingerprint EC-2.1 (Anarrhichomenum group) (Ordon˜ez et al, 2000). Isolates in group A were collected in the province of Pichincha, near the CIP station, between 1997 and 2004 ( Table 1).…”
Section: Pathogen Characterizationmentioning
confidence: 76%
“…Each of the three lineages has been described in detail: EC-1 (Forbes et al, 1997), US-1 (Oyarzun et a1., 1998), and EC-3 (Adler et al, 2004). Another pathogen group was described as the EC-2 clonal lineage (Ordon˜ez et al, 2000) but we have since identified new genotypes of P. infestans similar to EC-2 but differing in mating type and mtDNA haplotype. Clearly, the EC-2 group with its two mating type subgroups does not fit the definition of a clonal lineage and this population has subsequently been referred to as the Anarrhichomenum group, in reference to the series in the genus Solanum comprising the varied and poorly defined plant species that these pathogens attack (Adler et al, 2004).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Ecuador pear melon (Solanum muricatum) is generally attacked by the clonal lineage US-1, however on some locations is attacked by EC-2. Both populations showed high levels of virulence and correspond to two different genetic populations with different mating types and consequently there is a high risk of sexual recombination (Ordoñez et al, 2000). The mating type of the new haplotype is unknown, but if this is the case, we are facing a similar scenario involving sexual populations of the pathogen.…”
Section: Discussionmentioning
confidence: 99%